To Enhance the Fire Resistance Performance of High-Speed Steel Roller Door with Water Film System. (4th October 2015) - Chung, De-Hua; Wang, Tien-Chih; Tsai, Ming-Ju; Lin, Ta-Hui; Lee, Shin-Ku
Abstract : The structure of high-speed roller door with water film has improved in this study. The flameproof water film system is equipped with a water circulating device to reduce the water consumption of water film system. The water film is generated at the roller box of the high-speed roller door in this study. The heating test is done with the full-scale heating furnace. Both cases of the water film on unexposed surface and water film on exposed surface passed the fire resistance test based on ISO 834, proving that the high-speed roller door with water film system has 120A fire resistance period. The main findings indicate that the water film on exposed surface shows that as the amount of water film evaporated by high temperature inside the furnace must be greater than the evaporation capacity of water film on unexposed surface, the required water supply is 660 L more than the water film on unexposed surface.